Gestión y Oferta turística en la comunidad Guarguallá Chico , parroquia Cebadas. - Morocho Capusay, Jessica Patricia (2022)
ABSTRACT: The objective of this research was to analyze the management and tourism offer of the Guargualla Chico community, Parroquia Cebadas. The work is descriptive, correlational, analytical, its research design is non-experimental, causal correlational transverse, based on establishing the degree of influence existing between the management variable and the tourism offer variable; Two questionnaires were applied in a given period of time to collect the information. For the management variable, the officials of the Cebadas Parish Autonomous Decentralized Government and the Municipal Decentralized Autonomous Government of the Guamote Canton, in which the planning, organization and direction were evaluated; while for the variable Tourist offer to providers of tourist services (accommodation, food, guides, transport); Components of tourism products, tourism services and tourism infrastructure were evaluated, with the data acquired, the general hypothesis and the specific hypotheses were verified through the application of the Spearman Rho statistic, in which it is evidenced that the management is not related with the tourist offer. Finally, through the results obtained from the investigation and the carrying out of a situational diagnosis (SWOT) of the community, management strategies are proposed to improve the tourist offer of the Guarguallá Chico community, Parroquia Cebadas.